Analisis Faktor Pengaruh Pengungkapan Aset Biologis pada Perusahaan Perkebunan di Indonesia - Manik, April Tiodora (UMSurabaya Publishing, 2025)
Disclosure of biological assets in plantation companies in Indonesia remains inconsistent, despite detailed reporting guidelines in Statement of Financial Accounting Standards No. 69. This indicates a need to examine further the factors influencing the level of disclosure. The purpose of this research is to analyze the determinants that affect the disclosure of biological assets in plantation companies in Indonesia. The research method used is quantitative, processing numerical data to objectively assess relationships between variables. The study population comprises 17 plantation companies listed in Indonesia, and data analysis was conducted using descriptive statistical methods, with results presented in tables and processed using statistical software. The research period covers 2019 to 2024 to capture the development of biological asset disclosures after the pandemic. The study results reveal that the intensity of biological assets does not have a significant effect on disclosure levels. In contrast, company growth, leverage ratio, and public ownership are found to affect the level of biological asset disclosure positively.